2016
DOI: 10.1037/adb0000217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of vaping cannabis in a sample of young adults.

Abstract: Vaping nicotine (i.e., the use of e-cigarettes and similar devices to inhale nicotine) is becoming increasingly popular among young people. Though some vaporizers are capable of vaporizing cannabis, sparse research has investigated this method of cannabis administration. The present study examines the prevalence and correlates of vaping cannabis in a sample of 482 college students. Participants reported high lifetime rates of vaping nicotine (37%) and cannabis (29%). Men (r = 0.09, p = .047) and individuals fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 41 publications
7
85
5
Order By: Relevance
“…The present study also showed that marijuana users were significantly more likely to be past 30-day e-cigarette users, compared to non-users. Some studies suggest that vaping of cannabis extracts is becoming more common among marijuana users [19,35,36] due to its perception of being less harmful than the traditional burning to smoke methods [4], being easier to disguise due to reduced odours [35], and stimulating less throat irritation upon smoking [37]. Additionally, it is important to note that the current study utilizes results from a survey conducted in 2017, when cannabis was still considered an illegal substance in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed that marijuana users were significantly more likely to be past 30-day e-cigarette users, compared to non-users. Some studies suggest that vaping of cannabis extracts is becoming more common among marijuana users [19,35,36] due to its perception of being less harmful than the traditional burning to smoke methods [4], being easier to disguise due to reduced odours [35], and stimulating less throat irritation upon smoking [37]. Additionally, it is important to note that the current study utilizes results from a survey conducted in 2017, when cannabis was still considered an illegal substance in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research also suggests that medical users tend to use marijuana more frequently than non-medical users (Lankenau et al, 2017). Besides perceived therapeutic benefits, vape pens also are easier to use and offer greater discretion than other methods, which allows use in more places and contributes to greater likelihood of more frequent use (Jones et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Gendered patterns of cannabis use likely influence the risk of driving under the influence of cannabis. In one study, males were more likely to both vape and use cannabis edibles; and more frequent vaping was associated with driving under the influence [67]. As discussed above, in general, boys and young men tend to engage in riskier substance use behaviors.…”
Section: Driving Under the Influence Of Cannabismentioning
confidence: 94%